Correction of the excitation equations for hollow waveguides - A. A. Kurayev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The traditional excitation equations are based at the representation of excitating by extraneous sources field in form the sum of own waves TE ( H ) and TM ( E ) of the hollow waveguide, which transverses components form the complete basis in class of transverses vectors of section this waveguide. However in the sources area (longitudinal sonde, electron beam) the waveguide is not hollow and in this area exist potential transverse electric field. The transverse electric field expand the bases of E and H waves. This is not taken into account in the traditional excitation equations. In this paper the necessary correction of the excitation equations in sources area is performed.